2005
DOI: 10.1097/00000542-200501000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Cardiac Effects of Terlipressin, Vasopressin, and Norepinephrine on an Isolated Perfused Rabbit Heart

Abstract: On isolated rabbit heart, terlipressin induced a coronary vasopressor effect and in turn myocardial depression only at supratherapeutic concentrations (> or =30 nM). Its effects are mainly mediated via V1a receptors. However, these potential negative side effects on the heart were less pronounced than were those of AVP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 25 publications
1
33
1
2
Order By: Relevance
“…On the one hand, it is has been reported that heart-rate-dependent parameters of cardiac function (e.g. cardiac output) may be negatively influenced by vasopressin receptor analogs [5], and experimental evidence exists that infusion of vasopressin analogs dose-dependently induces coronary vasoconstriction [22], thereby suppressing coronary blood flow. In contrast, an experimental study in dogs demonstrated that AVP may induce endothelium-dependent relaxation of epicardial coronary arteries via V1 receptor-mediated nitric oxide release [23].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, it is has been reported that heart-rate-dependent parameters of cardiac function (e.g. cardiac output) may be negatively influenced by vasopressin receptor analogs [5], and experimental evidence exists that infusion of vasopressin analogs dose-dependently induces coronary vasoconstriction [22], thereby suppressing coronary blood flow. In contrast, an experimental study in dogs demonstrated that AVP may induce endothelium-dependent relaxation of epicardial coronary arteries via V1 receptor-mediated nitric oxide release [23].…”
Section: Discussionmentioning
confidence: 99%
“…Such observations have been confirmed in a model of isolated rabbit hearts without vasodilatory shock. 79 On the other hand, it is unlikely that AVP moderates excess edema in cardiac tissue, since V1R are the only subtype receptors expressed in the heart (along with oxytocin receptors), with no evidence of vasopressin-2 receptor or AQP-2 expression.…”
Section: Impact Of Ne and Avp On Myocardial Function And Ischemia In mentioning
confidence: 99%
“…However, in another porcine model of hemorrhagic shock that was performed to compare norepinephrine with vasopressin, norepinephrine was comparable to arginine vasopressin with respect to cerebral perfusion pressure and brain metabolism (20). In the current study, we chose norepinephrine as a vasopressor rather than vasopressin because hemorrhagic shock causes myocardial depression and norepinephrine has been shown to increase cardiac index and myocardial performance (21)(22)(23). Moreover, norepinephrine increases cerebral perfusion pressure immediately after hemorrhagic shock (20,24).…”
Section: Discussionmentioning
confidence: 99%